Glycoconjugate vaccines against antimicrobial resistant pathogens - Charlotte Sorieul; Marta Dolce; Maria Rosaria Romano; Jeroen Codée; Roberto Adamo (Taylor & Francis Group, 2023)
ABSTRACTIntroduction Antimicrobial resistance (AMR) is responsible for the death of millions worldwide and stands as a major threat to our healthcare systems, which are heavily reliant on antibiotics to fight bacterial infections. The development of vaccines against the main pathogens involved is urgently required as prevention remains essential against the rise of AMR.Areas covered A systematic research review was conducted on MEDLINE database focusing on the six AMR pathogens defined as ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Escherichia coli), which are considered critical or high priority pathogens by the World Health Organization (WHO) and the Centers for Disease Control and Prevention (CDC). The analysis was intersecated with the terms carbohydrate, glycoconjugate, bioconjugate, glyconanoparticle, and multiple presenting antigen system vaccines.Expert opinion Glycoconjugate vaccines have been successful in preventing meningitis and pneumoniae, and there are high expectations that they will play a key role in fighting AMR. We herein discuss the recent technological, preclinical, and clinical advances, as well as the challenges associated with the development of carbohydrate-based vaccines against leading AMR bacteria, with focus on the ESKAPE pathogens. The need of innovative clinical and regulatory approaches to tackle these targets is also highlighted.